Aspergillus fumigatus biofilms: Toward understanding how growth as a multicellular network increases antifungal resistance and disease progression. - Kaesi A Morelli (PLoS Pathogens, 2021)
Aspergillus fumigatus is a saprophytic, filamentous fungus found in soils and compost and the causative agent of several pulmonary diseases in humans, birds, and other mammals. A. fumigatus and other filamentous fungi grow as networks of filamentous hyphae that have characteristics of a classic microbial biofilm. These characteristics include production of an extracellular matrix (ECM), surface adhesion, multicellularity, and increased antimicrobial drug resistance. A. fumigatus biofilm growth occurs in vivo at sites of infection, highlighting the importance of defining mechanisms underlying biofilm development and associated emergent properties. We propose that there are 3 distinct phases in the development of A. fumigatus biofilms: biofilm initiation, immature biofilm, and mature biofilm. These stages are defined both temporally and by unique genetic and structural changes over the course of development. Here, we review known mechanisms within each of these stages that contribute to biofilm structure, ECM production, and increased resistance to contemporary antifungal drugs. We highlight gaps in our understanding of biofilm development and function that when addressed are expected to aid in the development of novel antifungal therapies capable of killing filamentous fungal biofilms.